Functional Properties of Microorganisms in Fermented Foods - Tamang, Jyoti P.; Shin, Dong-Hwa; Jung, Su-Jin; Chae, Soo-Wan (Frontiers in Microbiology, 2016)
Fermented foods have unique functional properties imparting some health benefits to consumers due to presence of functional microorganisms, which possess probiotics properties, antimicrobial, antioxidant, peptide production, etc. Health benefits of some global fermented foods are synthesis of nutrients, prevention of cardiovascular disease, prevention of cancer, gastrointestinal disorders, allergic reactions, diabetes, among others. The present paper is aimed to review the information on some functional properties of the microorganisms associated with fermented foods and beverages, and their health-promoting benefits to consumers.